2012
DOI: 10.3892/ijo.2012.1576
|View full text |Cite
|
Sign up to set email alerts
|

Akt expression and compartmentalization in prediction of clinical outcome in HER2-positive metastatic breast cancer patients treated with trastuzumab

Abstract: Trastuzumab is effective in about half of HER2-positive breast cancer patients. The PI3K/Akt signalling pathway plays an important role in the process of primary and secondary resistance to anti-HER2 targeted therapy. We evaluated the relationship between expression, activation and subcellular localization of selected Akt isoforms and response to trastuzumab-based anti-HER2 targeted therapy in patients with HER2-positive metastatic breast cancer. Seventy-four women with verified HER2-positive breast cancer wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
1
17
1
Order By: Relevance
“…We and others have shown that p473 Akt and p397 FAK co-localize at the invasive front of experimental mammary tumors and we found that this phenotype is lost if ECM cross-linking and stiffening is prevented (1,47). Here we determined that ECM stiffness mediates the localization and levels of these signaling molecules at the invasive front by activating vinculin.…”
Section: Resultssupporting
confidence: 52%
“…We and others have shown that p473 Akt and p397 FAK co-localize at the invasive front of experimental mammary tumors and we found that this phenotype is lost if ECM cross-linking and stiffening is prevented (1,47). Here we determined that ECM stiffness mediates the localization and levels of these signaling molecules at the invasive front by activating vinculin.…”
Section: Resultssupporting
confidence: 52%
“…In our study of human tumors, AKT1 mRNA expression correlated with both ER status and PIPP expression and was significantly decreased in triple negative breast cancers. Several other studies, however, have reported no correlation between AKT1 mRNA or protein expression and ER status (Creighton, 2007;Grell et al, 2012;Stå l et al, 2003), although pAKT1 levels were reported as higher in ER + than ER À tumors (Gershtein et al, 2007). In addition, increased AKT1 kinase activity has been reported in 45% of primary breast cancers (Sun et al, 2001).…”
Section: Discussionmentioning
confidence: 95%
“…demonstrated that AKT2 and pAKT (pSer473AKT) levels were associated with a lower distant recurrence rate. In the same line, Grell et al 45. showed that AKT2 expression and concurrent presence of pAKT (pThr308AKT and/or pSer473AKT) linked to better outcome in HER2 + metastatic patients treated with Trastuzumab.…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies that have associated AKT expression with cancer prognosis showed some contradictory results depending on the characteristics of the population evaluated and the technical approach454647. Pereira et al 47.…”
Section: Discussionmentioning
confidence: 99%